1995
DOI: 10.1002/cbf.290130211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypo‐ and hyperthyroidism on the function and metabolism of macrophages in rats

Abstract: The effect of thyroid hormones on monocyte migration, phagocytic capacity and hydrogen peroxide production by macrophages and the effect of these hormones on glutamine and glucose metabolism was investigated. The experiments were performed on resident, thioglycollate- and BCG-stimulated cells from hypo- and hyperthyroid rats. High plasma levels of thyroid hormones suppressed the migration of monocytes and hydrogen peroxide production, whereas hypothyroidism did not affect cell migration but raised the phagocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
1
19
0
3
Order By: Relevance
“…In rat macrophages, hyperthyroidism was shown to increase the rates of glucose uptake (28). In these cells, glycolysis was evaluated by measuring the activity of hexokinase and Krebs cycle by measuring the activity of citrate synthase and the decarboxylation of [U- 14 C]glucose (27)(28)(29). In macrophages from normal rats, insulin was shown to increase the activities of hexokinase and citrate synthase as well as the decarboxylation of glucose; in contrast, in macrophages from hyperthyroid rats, the activity of hexokinase was increased, whereas both the activity of citrate synthase and the decarboxylation of [U- 14 C]glucose were decreased suggesting an increase in the rates of glycolysis and a decrease in the rates of glucose oxidation (27)(28)(29).…”
Section: Effects Of Igf-i On Glut Isoformsmentioning
confidence: 95%
See 3 more Smart Citations
“…In rat macrophages, hyperthyroidism was shown to increase the rates of glucose uptake (28). In these cells, glycolysis was evaluated by measuring the activity of hexokinase and Krebs cycle by measuring the activity of citrate synthase and the decarboxylation of [U- 14 C]glucose (27)(28)(29). In macrophages from normal rats, insulin was shown to increase the activities of hexokinase and citrate synthase as well as the decarboxylation of glucose; in contrast, in macrophages from hyperthyroid rats, the activity of hexokinase was increased, whereas both the activity of citrate synthase and the decarboxylation of [U- 14 C]glucose were decreased suggesting an increase in the rates of glycolysis and a decrease in the rates of glucose oxidation (27)(28)(29).…”
Section: Effects Of Igf-i On Glut Isoformsmentioning
confidence: 95%
“…Several studies have shown that monocytes and macrophages utilize glucose at high rates and their metabolism is modified by insulin and thyroid hormones (25)(26)(27)(28)(29). In rat macrophages, hyperthyroidism was shown to increase the rates of glucose uptake (28).…”
Section: Effects Of Igf-i On Glut Isoformsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies in both human subjects and animal models have found that, similar to neutrophils, stimulated hyperthyroid macrophages have increased ROS production ex vivo (Videla et al 1993, Magsino et al 2000 although one study found an opposite effect (Rosa et al 1995). PTU treatment of hyperthyroid patients normalized ROS production although these findings could not be replicated in vitro (Videla et al 1993).…”
Section: Effects Of Extracellular Thyroid Hormone Levels On Macrophagmentioning
confidence: 99%